MEMPERJELAS EPISTEMOLOGI TAFSIR BI AL-MA’TSUR (Aplikasi Contoh Penafsiran dalam Jami’ al-Bayan Karya al-Tabari) - Zulfikar, Eko (Department of Alquran Science and Interpretation of the Faculty of Ushuluddin, Adab, and Da'wah of IAIN Langsa, 2019)
This paper discusses the epistemology of the bi al-ma?tsur interpretation from the book of Jami? al-Bayan ?An Ta?wil Ay al-Qur?an author by al-Tabari. The description covers how the author takes sources, methods, styles, and steps. As an interpretation of bi al-ma?tsur, this interpretation book contributes to a relative different approach from the previous mufassir. Al-Tabari in the interpretation is very dominant in using some histories such as the hadith of the Prophet, companions, and tabi?in, then he select strong opinions in accordance with what he wants. Based on the epistemology basis of bayani in terms of al-Jabiri, this paper will be supplemented with the evidences of the tafsir al-Tabari, how it really is. With descriptive-analytic study, it was found that the epistemology base is a combination of bi al-ma?tsur and bi al-ra?yi which expresses many perspectives before it has been chosen as the truth by al-Tabari. Other than that, the step of interpreting the Qur?an from the beginning to the end in the order of the manuscripts, and its discussion reviewed in detail and length, the book of tafsir al-Tabari is classified that it uses method tahlili.